2013
DOI: 10.1111/anu.12002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary nucleotides on the antioxidant status and serum lipids of rainbow trout (Oncorhynchus mykiss)

Abstract: An 8-week feeding experiment was conducted to evaluate the effects of dietary nucleotides (0, 0.5, 1, 1.5 and 2 g kg À1 ) on serum antioxidative biomarkers and lipid contents of rainbow trout fingerlings. The serum triglycerides and low-density lipoprotein (LDL)-C levels were significantly decreased in fish fed diets containing 1.5 and 2 g kg À1 , whereas serum high-density lipoprotein (HDL)-C was higher in trout receiving diets with those levels of nucleotides. A significant decrease in thiobarbituric acid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
(52 reference statements)
2
11
0
Order By: Relevance
“…Oncorhynchus mykiss in the previous studies (Mohebbi et al, 2013;Tahmasebi-Kohyani et al, 2011. However, the present study failed to observe growth promotion effect in rainbow trout fed 0.15% of purified nucleotides such as IMP, AMP, GMP, UMP and CMP.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Oncorhynchus mykiss in the previous studies (Mohebbi et al, 2013;Tahmasebi-Kohyani et al, 2011. However, the present study failed to observe growth promotion effect in rainbow trout fed 0.15% of purified nucleotides such as IMP, AMP, GMP, UMP and CMP.…”
Section: Discussionmentioning
confidence: 92%
“…Studies regarding the effects of dietary nucleotides in rainbow trout have been reported by Mohebbi, Nematollahi, Gholamhoseini, Tahmasebi-Kohyani, and Keyvanshokooh, (2013), Pasha-Zanoosi, (2011) andPasha-Zanoosi (2012). Those authors found that administration of nucleotides into fish diet promoted growth performance of fish when fish fed with high level of fish meal (43%) in the diet.…”
mentioning
confidence: 99%
“…In this context, Mohebbi et al. () reported that dietary NT supplementation led to an increase in plasma HDL in rainbow trout ( Oncorhynchus mykiss ). Moreover, after ESA, hemolymph HDL concentration significantly increased in all groups might be as a consequence of increasing mobilization of lipids from the hepatopancreas to the ovaries.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, Mohebbi et al (2013) reported that dietary NT Initial 108.9 ± 11.0 108.9 ± 11.0 108.9 ± 11.0 108.9 ± 11.0 0.001 0.146 1.0…”
Section: Plasma Biochemical Parametersmentioning
confidence: 97%
“…(Wu et al, 2011 andMohebbi et al, 2013). In contrast, limited information is available in the literature about the need for nucleotides and their role in poultry.…”
Section: Introductionmentioning
confidence: 99%